2015
DOI: 10.2166/wh.2015.210
|View full text |Cite
|
Sign up to set email alerts
|

Study of phosphate removal from aqueous solution by zinc oxide

Abstract: Zinc oxide (ZnO) was synthesized and used to investigate the mechanism of phosphate removal from aqueous solution. ZnO particles were characterized by X-ray diffraction, scanning electron microscope and Fourier transform infrared spectroscopy before and after adsorption. Batch experiments were carried out to investigate the kinetics, isotherms, effects of initial pH and co-existing anions. The adsorption process was rapid and equilibrium was almost reached within 150 min. The adsorption kinetics were described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…Phosphorus adsorption capacities and phosphorus removal efficiency, R, (%) were determined from the Equations (3) and (4) respectively: where V (mL) represents the working solution volume, C 0 and C e (mg/L) are the concentrations in the working solution (initial phosphorus concentration) and filtrate (equiibrum phosphorus solution), respectively, and m (g) is the adsorbent amount [ 89 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phosphorus adsorption capacities and phosphorus removal efficiency, R, (%) were determined from the Equations (3) and (4) respectively: where V (mL) represents the working solution volume, C 0 and C e (mg/L) are the concentrations in the working solution (initial phosphorus concentration) and filtrate (equiibrum phosphorus solution), respectively, and m (g) is the adsorbent amount [ 89 ].…”
Section: Methodsmentioning
confidence: 99%
“…The specific procedure was as follows: 0.1 g of each adsorbent material was weighed into a 50 mL Erlenmeyer flask, 15 mL of a set concentration of phosphorus solution was added, and the pH of the solution was adjusted to 7.5 with 0.1 mol/L hydrochloric acid or 0.1 mol/L sodium hydroxide solution. The solution was shaken in a constant temperature shaker at 180 r/min and 25 °C for 24 h. A syringe was used to take out 10 mL of the supernatant from the Erlenmeyer flask and filter it with a 0.45 µm filter membrane; the phosphorus concentration in the filtrate was determined by ammonium molybdate spectrophotometry (950 Lambda UV-Vis-NIR Perkin Elmer, Waltham, MA, USA), and the removal capacity of phosphorus and phosphorus removal efficiency of each adsorbent was calculated according to Equations (3) and (4) [ 83 , 89 ]. A single-factor analysis method was used and blank and two parallel experiments were carried out.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar study conducted by ma et al has shown that the morphology of MgO could be varied with the time at which the reaction is taken place at a particular temperature. [97] The product yield was increased up to 62 %, followed by repetitive autoclavation of the supernatant. The SEM images showed a phase change from MgO nanowires to nanoflakes.…”
Section: Evaluation Of the Mechanistic Aspects Of Monf Formation And ...mentioning
confidence: 99%
“…For various contact times, the P ion residual concentration was calculated (from 0 min to 24 h). The following equations (11)(12)(13)(14) were used to assess the adsorption data toward phosphorous following the kinetic models:…”
Section: Kinetic and Thermodynamic Studiesmentioning
confidence: 99%